Efficient sky-blue radioluminescence of microcrystalline Cs3Cu2I5 based large-scale eco-friendly composite scintillators for high-sensitive ionizing radiation detection. (5th May 2021) - Ouyang, Xiao; Lin, Richeng; Ding, Ying; Liang, Yali; Zheng, Wei; Chen, Liang; Song, Xiaojing; Huang, Feng; Ouyang, Xiaoping
Abstract : A high-efficiency sky-blue radioluminescence, large-size, eco-friendly hybrid scintillator made of CsI:Na and Cs3 Cu2 I5 single crystals is expected to become a potential ionizing radiation detection scintillator. Abstract : Nontoxic scintillators with high brightness are greatly desired for use in reliable, affordable and eco-friendly scintillant detectors used for ionizing radiation detection in the security, nuclear control, medical diagnosis and high-energy physics fields. Here, a large-scale eco-friendly composite scintillator combining CsI:Na and Cs3 Cu2 I5 crystals exhibits a high-brightness sky-blue radioluminescence. This phenomenon is based on a perfect optical conversion (wave-shift) mechanism, through which the ultraviolet radioluminescence of CsI can be efficiently transferred to visible sky-blue radioluminescence (centered at 455 nm) with a light yield of as high as 57.5k photon per MeV, which is 2.4 times higher than that of commercial CsI (Na) single crystals and even exceeds that of commercial CsI:Tl (54.0k photon per MeV), thus greatly improving the detection quantum efficiency of terminal photodetectors. In addition, the as-prepared composites replace the toxic heavy-atom Pb, which makes it feasible to prepare large-size scintillation screens through a simple operation. All the above-mentioned findings prove their potential for applications in next-generation eco-friendly scintillators for ionizing radiation detection in the future.